2022
DOI: 10.3389/fnbeh.2022.896545
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Workplace Environment on Coal Miners’ Emotion and Cognition Depicted in a Mouse Model

Abstract: Most coal mine accidents are caused by the unsafe behavior of employees. Previous studies have shown that there is a significant connection among the working environment, the psychological state of employees, and unsafe behaviors. However, the internal biological mechanism has not been revealed. To explore the physiological and psychological alterations of coal mine workers and the underlying mechanisms that cause unsafe behaviors, the current study established a novel coal mine environment biological simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Various prevention and control strategies for miners’ unsafe states can quickly reduce the level of miners’ unsafe behavior and reduce the risk of unsafe behavior. This research result is consistent with the research conclusions of previous scholars [ 23 , 69 ]. A long-term working environment of the deep coal mine and complex production process will cause negative changes in miners’ safe state.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Various prevention and control strategies for miners’ unsafe states can quickly reduce the level of miners’ unsafe behavior and reduce the risk of unsafe behavior. This research result is consistent with the research conclusions of previous scholars [ 23 , 69 ]. A long-term working environment of the deep coal mine and complex production process will cause negative changes in miners’ safe state.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, relevant studies have confirmed that the hot and humid underground climate in deep mines not only seriously affects the physical and mental health of miners but also reduces the production efficiency of miners and increases the safety risk of deep mining [ 22 ]. Li et al also showed through a mouse biological simulation model experiment (CEBS) that environmental factors such as temperature, humidity, and noise in coal mine workplaces could lead to adverse reactions, such as anxiety, depression, and impaired memory ability in mice [ 23 ]. From the above analysis, the harsh working environment, such as high temperature, high humidity, noise, and dust in the underground coal mine, combined with high-intensity physical labor, will cause coal miners to suffer from various occupational diseases and destructive emotions.…”
Section: Introductionmentioning
confidence: 99%
“…The emotions involved in this study primarily refer to negative emotions. Li et al verified, by simulating the underground environment of a coal mine, that anxiety and depression will put the miners in an unsafe state, thus prompting the miners to engage in unsafe behaviors [55]. Coal mine practitioners driven by negative emotions are in an unsafe state.…”
Section: Results Analysismentioning
confidence: 99%